Marketing Strategy Planning Based on Customer Value - Gilang Fatikhul Burhan; Agus Mansur (PROZIMA (Productivity, Optimization and Manufacturing System Engineering), 2020)
Determination of marketing strategies is crucial in the process of running a company. The concept of customer value has become increasingly used in marketing strategies and literature in recent years. Understanding customer needs and desires is very important in designing effective market strategies. Strategy makers must consider the complexity of factors when evaluating and choosing marketing strategies. CV Rumah Mesin is a company engaged in the supply and manufacture of various types of machinery. CV Rumah Mesin has difficulty in maintaining sales consistency which has an impact on sales turnover. The purpose of this study is to identify the level of performance and consumer expectations of products and services at CV Rumah Mesin and develop appropriate marketing strategies based on the results of identifying the performance and expectations of consumers. The method used in this research is Modified Servqual and AHP. From the results of the analysis and discussion of research that has been done, it can be concluded that there are several factors that must be improved by the company such as the guarantee of machine products, the safety of machine products, the safety of product shipments, the availability of varied machine products, and the company will never be busy (ignoring ) response from consumers. In marketing its products, company can use the target market segmentation strategy to consumer agencies such as the industry service and the tourism service. Companies can provide responsive post-sale services in providing certain guarantees to consumers in an effort to differentiate from competing companies